Profesi Pengatur Belokan Jalan Dalam Perspektif Ekonomi Syariah (Studi Fenomenologi Di Persimpangan SMPN 2 Purwakarta) - Nurhayati, Rina; Suryana, Eka Ahadiyat; Suryadi, Aji (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2024)
Based on the results of the author's observations, the profession of road turn regulator does not have the legal auspices of the Constitution, in contrast to parking attendants who already have legal auspices under the guidance of the Department of Transportation of each city or region. The second phenomenon is the job security of the road turn regulator profession at the SMPN 2 Purwakarta Road Intersection, Kel. Ciseureuh Purwakarta has not been guaranteed, either health insurance or work accident insurance. The purpose of this study was to determine the profession of road turn regulator at the intersection of SMPN 2 Purwakarta in sharia economic perspective. This research uses qualitative methods with a phenomenological approach, data collection through observation, interviews with 5 respondents who have met the criteria, documentation studies. The results of the study can be concluded that "Pak Ogah" is a term for those who work as workers who regulate almost every road intersection. The income they get from each driver ranges from Rp. 500,- to Rp. 2,000,- and sometimes there are drivers who deliberately give more. This income if calculated within one hour is at least Rp. 50,000, - up to Rp. 200,000, - depending on the crowd in the center of Purwakarta City. The profession of the road turn regulator at the SMPN 2 Purwakarta road intersection is not yet in accordance with sharia economics, because the road turn regulator at the SMPN 2 Purwakarta road intersection who carries out his duties is only limited to pursuing gifts from 2-wheeled drivers, especially 4-wheeled ones, besides that many are also found that the position and instructions of the road turn regulator are not based on traffic safety and order.